The intergenerational transmission of education: A case study from Iceland - Emil Dagsson; Thorlakur Karlsson; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2018)
We estimate the relation between parents' education on the education of their children using survey data from Iceland. We find a positive correlation between the education of parents and their children as well as a positive correlation between parents' emphasis on the importance of education and their children's education. The mother's education appears to matter more than that of the father. The correlation between the educational levels is lower than in other countries, including the egalitarian Nordic countries, which suggests a weaker transmission between generations. Moreover, parents who have not received higher education can influence the choices made by their children by emphasizing the importance of education to them.
Keywords: I21; J13; 330; Education; generations; transmission; Intergenerationale Übertragung; Bildungsniveau; Island